(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Self-care among diabetes is met with a lot of obstacles and challenges including unclear advices from medicalpractitioners, non-cooperation from family members, financial constraints, the accessibility to health centres, and cultural differencesbetween families and the health‑care provider.Objectives: To assess the self-care practices among male and female diabetic patients in the urban filed practice area of tertiary teachinghospital. To determine the predictors of self-care practices among diabetic patients.Methods: A community based cross-sectional study was conducted in Urban Field Practice area attached to the department ofCommunity Medicine, Konaseema Institute of Medical Sciences and Research Foundation, Amalapuram among Type 2 diabeticpatients who were on treatment for at least 1 year aged 18 years and above during the months of February and March 2022. Data wascollected using predesigned semi structured questionnaire using interview technique after taking informed consent. Self-care practiceswere evaluated from The Summary of Diabetes Self-care Activities (SDSCA) Measure. Data was entered and analysed using Microsoftexcel and SPSS ver. 20 software.Results: Half of the study subjects had good self-care followed by 35% had moderate and rest had poor self-care. There was astatistically significant difference between the self –care practices among male and female subjects.Conclusion: The present study concluded that overall self-care was good among half of the study subjects, but individual self-carepractices were not that good. Increased age, higher education, duration of diabetes and social class were identified as good predictorsof level of self-care in Diabetes.